CD-ROMs and beyond : buying databases sensibly? - MC SEAN, Tony (1992)
Examines the reasons why CD-ROM technology has made such a widespread impact in the science, technology and medicine sectors. Looks at its limitations, and sees it as a producer's technology - cheap to produce in volume, impractical to pirate.